31. CRITICAL THINKING ABILITY OF NURSING STUDENTS AT PHAM NGOC THACH UNIVERSITY OF MEDICINE (Vietnam Journal of Community Medicine, 2025)
Objective: Determine the average level of critical thinking ability and related factors among nursing students at Pham Ngoc Thach University of Medicine during the 2024-2025 academic year.Method: A cross-sectional study was conducted on 288 full-time nursing students from first to fourth year at Pham Ngoc Thach University of Medicine during the 2024-2025 academic year. The 40-item short version of the Watson and Glaser Critical Thinking Appraisal was used for assessment.Results: The average critical thinking score among students was 24.85 ± 3.88. Of the participants, 64.2% fell into the weak critical thinking group (< 27 points), 30.9% into the moderate group (27-30 points), and only 4.9% reached the good level (≥ 31 points). Critical thinking ability showed statistically significant differences by academic year (p = 0.001) and gender (p = 0.005), but was not significantly associated with self-study hours (p = 0.179).Conclusion: Nursing students’ critical thinking ability remains limited, with the majority scoring at a low level. The significant differences observed by academic year and gender highlight the necessity of incorporating critical thinking development into nursing education programs to enhance students’ cognitive skills.
Keywords: Critical thinking ability; nursing students; Watson and Glaser.